2005
DOI: 10.1111/j.1525-1438.2005.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete remission of an endometrial carcinoma with bilateral multiple pulmonary and extrapelvic metastases treated by surgery and chemotherapy consisting of paclitaxel and carboplatin

Abstract: Successful management of a patient with endometrioid type, grade 2 endometrial carcinoma with bilateral multiple pulmonary and extrapelvic abdominal metastases has been reported. A 61-year-old woman with the preoperative diagnosis of stage IVB endometrial carcinoma underwent surgery followed by six cycles of chemotherapy consisting of paclitaxel (175 mg/m2) and carboplatin (area under curve 5). After the sixth course, there were no abnormal findings on chest and abdominal computed tomography. She has no eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Brain involvement in EC is rare and is usually considered a late event. In the series reported in the literature, the incidence of brain metastases ranges from 0.3-0.9% [11,14,15,22,23,50], which is in accordance with the value of 0.6% (10/1610) in our group of patients.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Brain involvement in EC is rare and is usually considered a late event. In the series reported in the literature, the incidence of brain metastases ranges from 0.3-0.9% [11,14,15,22,23,50], which is in accordance with the value of 0.6% (10/1610) in our group of patients.…”
Section: Discussionsupporting
confidence: 73%
“…In the literature, the survival rate for these patients is generally poor, with 1-year survival rates of 20-30% and 5-year survival rates of less than 10% [6,8,9,20,23,42,50].…”
Section: Hm To the Lungmentioning
confidence: 99%
See 2 more Smart Citations
“…also reported that current chemotherapy drugs are minimally effective for uterine LMS 13 . These observations definitely differ from observations in endometrial cancer, in which combination chemotherapy appears to be the optimal treatment modality in pulmonary metastasis after primary surgery for hysterectomy 14–16 …”
Section: Discussionmentioning
confidence: 96%